Jenseits der Grenzen : Beiträge zur spätantiken und frühmittelalterlichen Geschichtsschreibung - Goltz, Andreas (2009)
The process of transformation which saw the Byzantine Empire and the world of the Early Middle Ages develop from the Late Antique Imperium Romanum led to changes in all areas of life. The central topic of this volume of international contributions is the question of how the historiography of the period confronted these changes.